2020
DOI: 10.1155/2020/7895293
|View full text |Cite
|
Sign up to set email alerts
|

Bu-Shen-Yi-Sui Capsule, an Herbal Medicine Formula, Promotes Remyelination by Modulating the Molecular Signals via Exosomes in Mice with Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis (MS) is a common inflammatory demyelinating disorder of the central nervous system. Bu-shen-yi-sui capsule (BSYSC) could significantly reduce the relapse rate, prevent the progression of MS, and enhance remyelination following neurological injury in experimental autoimmune encephalomyelitis (EAE), an established model of MS; however, the mechanism underlying the effect of BSYSC on remyelination has not been well elucidated. This study showed that exosomes carrying biological information are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…MBP results show that BSYSC can effectively promote the differentiation of OPCs and combined with LFB staining show that BSYSC significantly increases the myelin sheath density in the corpus callosum area. These results indicate that BSYSC exerts a neuroprotective effect in EAE mice, which is consistent with our previous experimental results [ 10 , 33 , 44 ] and provides a basis for the clinical application of this formula.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MBP results show that BSYSC can effectively promote the differentiation of OPCs and combined with LFB staining show that BSYSC significantly increases the myelin sheath density in the corpus callosum area. These results indicate that BSYSC exerts a neuroprotective effect in EAE mice, which is consistent with our previous experimental results [ 10 , 33 , 44 ] and provides a basis for the clinical application of this formula.…”
Section: Discussionsupporting
confidence: 92%
“…Adult SD rats were randomly divided into the following two groups: (1) the normal control (NC) group, which was treated with distilled water, and (2) the BSYSC group. BSYSC powder was dissolved in distilled water (11.7 g raw herb/kg) and through gastric tubes twice per day for 7 days [ 10 , 44 ], the rats were administered 11.7 g/kg BSYSC through gastric tubes twice per day for 7 days. Two hours after the BSYSC treatment on day 7, blood was collected from the abdominal aortas of the rats into polypropylene tubes and incubated at 4°C for 4 h. The subsequent steps were the same as in previous studies [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies found that BSYS could ameliorate demyelination and axon injury by regulating Th17/Treg cells [28] and promoting oligodendrocyte progenitor cell (OPC) maturation [29,30]. This study is aimed at evaluating the neuroprotective effects of BSYS on EAE mice and potential mechanisms of microglial polarization regulated by BSYS.…”
Section: Introductionmentioning
confidence: 99%
“…BSYS Capsule was provided by Asia-East Biopharmaceutical Co., Ltd. (Beijing, China). We employed previously described steps to obtain the BSYS drug-containing serum (BSYS serum) and blank serum [ 28 ]. Adult Sprague-Dawley (SD) rats weighing between 180 and 220 g were maintained in a specific pathogen-free condition.…”
Section: Methodsmentioning
confidence: 99%